2020
DOI: 10.1021/acsomega.0c04070
|View full text |Cite
|
Sign up to set email alerts
|

Toughening of Poly(l-Lactide) with Branched Polycaprolactone: Effect of Chain Length

Abstract: In this work, a series of branched polycaprolactone (BPCL) samples with different ε-caprolactone (CL) chain lengths were synthesized and used to toughen poly (lactic acid) (PLA). The spherical structure increased the free volume, facilitating the free movement of the PLA chain segment and increasing the ductility. In addition, the hydrogen bonds between the multiterminal hydroxyl group of BPCL x and PLA improved the interaction between them. The glass-transition temperatures (T g ) and crystallization temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 48 publications
1
38
0
Order By: Relevance
“…4 Yang et al also concluded similar results, they observed increments with the increase of chain length at first, but then a decrement was observed especially in toughness because of chain entanglements. 29 Likewise, Liu et al determined 15% branched PCL content as optimal concentration to toughen PLA without injuring other properties such as tensile strength, crystallization, and rheological behaviors. 34 The yield strength increased with PLA/SPLA blends prepared at 95/5 and 90/10 ratios, but there was no significant change with blends prepared at 80/20 ratio.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
See 4 more Smart Citations
“…4 Yang et al also concluded similar results, they observed increments with the increase of chain length at first, but then a decrement was observed especially in toughness because of chain entanglements. 29 Likewise, Liu et al determined 15% branched PCL content as optimal concentration to toughen PLA without injuring other properties such as tensile strength, crystallization, and rheological behaviors. 34 The yield strength increased with PLA/SPLA blends prepared at 95/5 and 90/10 ratios, but there was no significant change with blends prepared at 80/20 ratio.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…26 It is given in the literature that polymers with different branched three-dimensional structures improved the processing and mechanical properties of PLA. [27][28][29][30][31][32][33][34] Deokar et al prepared different molecular weight multiarmed star copolymers with PLA and PCL. The elongation enhanced with the increment of arm number of the copolymers.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations